Drivers of Urban Agriculture and their Influence on the Socio-Economic Status of the Urban Farmers in Uganda, A Case Study of Kampala and Mbarara Cities - Ninsheka, Leonard; Ssemakula, Edward; Tiyo, Christopher; Kalibwani, Rebecca; Mulongo, Marius (International Journal of Clinical Science and Medical Research, 2024)
The study analyzed the influence of forms and drivers of urban Agriculture on the socio-economic status of the farmers in Kampala and Mbarara Cities. The specific objective of the study was to examine the influence drivers of urban agriculture on the socio-economic status of farmers. The study adopted a cross-sectional research design using multiple data collection methods. A multistage cluster sampling technique involving simple random sampling to get both primary and secondary sampling units, snowball to get target respondents and purposive sampling for key informants and focus group members was used. Data were collected using social survey questionnaires for households, focus group discussions checklist (FGDs), key informant interview guides and observations, from a sample of 384 respondents. The study found a strong association between drivers of UA and the socioeconomic status of the urban farmers in Kampala and Mbarara Cities. Household socio-economic status has substantially correlated with the drivers of the urban farmers and out of 9 items considered only 5 was significant which include access to capital (x2 = 1.175, p< 0.047), access to agriculture extension services (x2 = 3.634, p< 0.026), access to financial grants (x2 = 5.190, p<0.001), access to markets (x2 = 6.993, p< 0.001), value addition(x2 = 3.718, p<0.014). The study confirmed a significant relationship between drivers of urban agriculture and the socio-economic status of urban farmers. Urban agriculture drivers like access to capital and financial grants, nature of market access and value addition had a significant influence on household socio-economic status.